Potent and Persistent Antibody Response in COVID-19 Recovered Patients - Tian, Xiaodong; Liu, Ling; Jiang, Wenguo; Zhang, He; Liu, Wenjun; Li, Jing (Frontiers in Immunology, 2021)
SARS-CoV-2 has caused a global pandemic with millions infected and numerous fatalities. Virus-specific antibodies can be detected in infected patients approximately two weeks after symptom onset. In this study, we set up ELISA technology coating with purified SARS-CoV-2 S and N proteins to study the antibody response of 484 serum samples. We established a surrogate viral inhibition assay using SARS-CoV-2 S protein pseudovirus system to determine the neutralization potency of collected serum samples. Here, we report robust antibody responses to SARS-CoV-2 in 484 recovered patients varying from 154 to 193 days, with 92% of recovered patients displaying a positive virus-specific spike glycoprotein IgG (s-IgG) response, while the ratio of positive spike glycoprotein IgM (s-IgM) reached 63%. Furthermore, moderate to potent neutralization activities were also observed in 62% of patients, correlating significantly with s-IgG response. This study strongly supports the long-term presence of antibodies in recovered patients against SARS-CoV-2, although all serum samples were collected from individuals with mild or moderate symptoms.